Implementasi Penilaian Autentik Pada Pembelajaran Ilmu Pengetahuan Sosial Di Madrasah Tsanawiyah - Noor Fatmawati; Mu'ayyadah Mu'ayyadah; Dany Miftah Nur (Sosio-Didaktika: Social Science Education Journal, 2021)
Authentic assessment as a form of assessment in the 2013 curriculum. The object of study is through the implementation of an authentic assessment, the constraints and solutions proposed for each problem. One of the reasons for this gap is the multi-character, multi-understanding factor and the students. Basically, the method of interviewing and observing social studies teachers is called descriptive qualitative research. This study aims to reveal authentic assessments and understand the situation in the field how authentic assessments are carried out. In addition, the potential difficulties encountered during the assessment by the teacher and the solutions determined. The results show that social studies teachers at MTs NU Miftahul Falah Kudus have a perception of authentic assessment that has 3 components, namely knowledge, skills, and attitudes. However, it still has several obstacles, namely the limited skills of teachers in learning variations, lack of enthusiasm of students, material that is difficult to understand, problems in learning media, application of evaluation systems, and limited facilities. The solution is teacher openness in assessment, namely: teachers must be transparent in assessing.